Knowledge, attitudes and practices of school children with regards to beans. - Rodríguez, Shirley (2004)
The present study identifiesknowledge, attitudes and practices with regards to beans inschool children attending third and fourth grades. Anadditional test about attitudes was carried out with schoolchildren of first, second and third grades. The study wasconduced in 1998 in Sabanilla de Montes de Oca, an urbancommunity of Costa Rica. The study was part of an initialassessment done before developing an educational Campaignaimed at increasing bean consumption. Qualitative andquantitative methodologies were used for this purpose. Thestudy found that children had basic knowledge of thenutritional value of beans, and that most of them liked beans.However, almost 10% of the children refused to eat them, andthis attitude was found to be stronger as their age increased.The study also identified other barriers that limit beanconsumption in school children, many of whom wereinfluenced by negative attitudes of adults, or because thisfood was not available at home. This information wasimportant in the planning of the previously mentionededucational Campaign, in which children had been selectedas an interactive group because of their close contact withtheir mothers.